Peeled - Bauer, Joan 1951- (New York G.P. Putnam's Sons, 2008)
In an upstate New York farming community, high school reporter Hildy Biddle investigates a series of strange occurrences at a house rumored to be haunted.
Keywords: Reporters and reporting -- Juvenile fiction; Journalism -- Juvenile fiction; Farm life -- New York (State) -- Juvenile fiction; Haunted houses -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; New York (State) -- Juvenile fiction